Physical and Tensile Properties of Handmade Sida rhombifolia Paper - P. W. Huisken Mejouyo; E. Dydimus Nkemaja; O. R. Beching; N. R. Sikame Tagne; T. Kana’a; E. Njeugna (International Journal of Biomaterials)
This study focuses on the production and characterization of biodegradable handmade paper from the Sida rhombifolia plant (SRP) cellulose. Sida rhombifolia plant is a seasonal plant that grows in the equatorial and tropical climates. The studies carried out on this SRP were aimed at investigating the methods required for the production of handmade paper from SRP plant and also at determining the tensile strength. Four specimens of SRP paper of different additive labels S0 (no additive), S1 (starch and KOH), S2 (starch), and S3 (Foska liquid glue) were produced using the Kraft method. Tensile properties (stress at break, elongation at break, and Young’s modulus), the rate of water absorption, and the rate of moisture absorption were carried out. Results showed that the addition of potassium hydroxide considerably reduces Young’s modulus of SRP handmade paper (S1) while the Foska liquid glue (S3) significantly improves it. In addition, the addition of potassium hydroxide and Foska liquid substantially improves the water absorption properties of the paper S2 and S3, respectively. The adhesive liquid creates more porosity and consequently increases the absorption of water. The addition of potassium hydroxide and Foska liquid significantly embedded the rate of moisture absorption. From the results obtained, it can be concluded that the paper S3 can be used as packaging paper since it has better mechanical properties and moisture absorption.